Alternative regimens for prostate cancer treatment using radiation therapy - Oliveira, S. M. (2012)
Purpose/Objective: The purpose of this work was to determine biologically equivalent alternative regimens for the treatment of prostate cancer using External Beam Radiotherapy (EBRT) and Low Dose-Rate Brachytherapy (LDRBT) with 125I implants and to evaluate the sensitivity of these regimens to different sets of radiobiological parameters of the Linear-Quadratic (LQ) model.